Pendekatan Structural Equation Modelling (SEM) dalam Operasi Logistik : Studi Kasus Operasi Amfibi TNI Angkatan Laut - Yahya Prasetyo; Marthin Luther; Etwin Ramadhan; Jumino Jumino (Rekayasa, 2022)
Along with the development of naval technology, the roles, tasks and functions of the support of the Motorized Transport Battalion (Yon Angmor) have the complexity and dynamics of movement in supporting the implementation of Amphibious Operations, which are very important and have high traffic. In this study, conducted to identify and analyze organizational readiness, readiness in the field of Operations as an element of Satbanmin, and the readiness in the field of Logistics as an element of Satbanmin in the implementation of Amphibious Operations. The results of the measurement using SEM AMOS 23 software from the measurement model of the three variables of operational readiness, organizational readiness and logistical support readiness that affect administrative assistance support, that the operational readiness variable produces the highest value of 0.566. This means that the implementation of the operational readiness of the Yon Angmor in supporting administrative assistance in Amphibious operations can be carried out optimally and according to SOPs, despite having obstacles and problems in organizational readiness. So, to answer the existing problems, the Yon Angmor needs to plan the formation of an organization through organizational validation, as well as calculating risk management in supporting administrative assistance in the implementation of comprehensive amphibious.